Conducting national burden of disease studies and knowledge translation in eight small European states: challenges and opportunities - Cuschieri, Sarah; Alkerwi, Ala'a; Economou, Mary; Idavain, Jane; Lai, Taavi; Lesnik, Tina; Meyers, Caine; Samouda, Hanen; Sigfúsdóttir, Inga Dóra; Terzic, Natasa; Tzivian, Lilian; Pallari, Elena (My University, 2022)
Background: Several countries across Europe are engaging in burden of disease (BoD) studies. This article aims to understand the experiences of eight small European states in relation to their research opportunities and challenges in conducting national BoD studies and in knowledge translation of research outputs to policy-making. Methods: Countries participating in the study were those outlined by the WHO/Europe Small Countries Initiative and members of the Cooperation in Science and Technology (COST) Action CA18218 European Burden of Disease Network. A set of key questions targeting the research landscape were distributed to these members. WHO’s framework approach for research development capacities was applied to gain a comprehensive understanding of shortages in relation to national BoD studies in order to help strengthen health research capacities in the small states of Europe. Results: Most small states lack the resources and expertise to conduct BoD studies, but nationally representative data are relatively accessible. Public health officials and researchers tend to have a close-knit relationship with the governing body and policy-makers. The major challenge faced by small states is in knowledge generation and transfer rather than knowledge translation. Nevertheless, some policy-makers fail to make adequate use of knowledge translation. Conclusions: Small states, if equipped with adequate resources, may have the capacity to conduct national BoD studies. This work can serve as a model for identifying current gaps and opportunities in each of the eight small European countries, as well as a guide for translating country BoD study results into health policy.
Keywords: Burden of disease; Knowledge translation; Small countries; Research